The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Environmental Engineering and Activated Sludge Processes 2016
DOI: 10.1201/b19902-3
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Approaches for the Surface Interaction between Copper and Activated Sludge Microorganisms at Molecular Scale

Abstract: Interactions between metals and activated sludge microorganisms substantially affect the speciation, immobilization, transport, and bioavailability of trace heavy metals in biological wastewater treatment plants. In this study, the interaction of Cu(II), a typical heavy metal, onto activated sludge microorganisms was studied in-depth using a multi-technique approach. The complexing structure of Cu(II) on microbial surface was revealed by X-ray absorption fine structure (XAFS) and electron paramagnetic resonanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…41 The g values suggested that the distorted square pyramidal octahedral coordination of copper within the siliceous framework demonstrating the copper (II) complex (Figure S2). 58 The fluorescence spectra explored the absorption characteristics of Dox along with its coordination to the mesoporous framework (Figure 4D). The sample specimens were excited at an absorption maximum of Dox (λ ex : 440 nm) and resulted in maximum emission at around 580 nm (λ em ) 40 (Figure 4D-a).…”
Section: Resultsmentioning
confidence: 99%
“…41 The g values suggested that the distorted square pyramidal octahedral coordination of copper within the siliceous framework demonstrating the copper (II) complex (Figure S2). 58 The fluorescence spectra explored the absorption characteristics of Dox along with its coordination to the mesoporous framework (Figure 4D). The sample specimens were excited at an absorption maximum of Dox (λ ex : 440 nm) and resulted in maximum emission at around 580 nm (λ em ) 40 (Figure 4D-a).…”
Section: Resultsmentioning
confidence: 99%
“…The FT-IR spectra of extracellular proteins also revealed that some carbohydrates and nucleic acids could bind with proteins. Many previous studies showed the high binding activity of EPS toward metal ions, dyes and pharmaceutical 23 24 25 26 . Figure 5 shows the protein amounts related to binding activity (organic molecules and ions) in anaerobic sludge and aerobic sludge were similar, whereas they were more abundant than those in anoxic sludge.…”
Section: Discussionmentioning
confidence: 99%
“…The adsorption process of Cu(II) and Pb(II) from aqueous solution onto the raw and the treated MK was described by the Langmuir isotherm equation, which has been widely used in previous studies to explore the adsorption isotherms and to determine the maximum adsorption capacity of sorbent materials toward pollutants [8,17,18]. Following is a linearized form of the Langmuir isotherm: ); e q is the amount of Cu(II) or Pb(II) adsorbed at equilibrium (mg g -1 ); max q is the maximum adsorption capacity of MK at equilibrium (mg g -1 ); and b (L mg -1 ) is the Langmuir constant [19,20]. were involved in the hydrothermal reactions of raw MK.…”
Section: Batch Sorption Experimentsmentioning
confidence: 99%